Magnetic powder core material and preparation method and application thereof
By optimizing the coating process of the magnetic powder core material, the magnetic powder core material that forms a water-repellent film is solved, and the existing magnetic powder core rusts in high-temperature and high-humidity environments are achieved, achieving the need for stable inductance characteristics and long-term use.
Patent Information
- Application Number
- CN202311239487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The existing magnetic powder core is prone to rust in high temperature and high humidity environments, resulting in the change rate of inductance characteristics exceeding ±10%, which cannot meet the stability requirements of long-term use and harsh environmental conditions.
By optimizing the material coating process, metal magnetic powder core raw materials, silicon sol, phosphorus source, glue and mold release powder are used to form magnetic powder core materials with a water-repellent film on the surface to ensure that the magnetic powder core does not corrode in a high temperature and high humidity environment.
The anti-rust effect of the magnetic powder core is achieved, the inductance characteristic change rate is controlled at ±2%, and stored at 85℃ for 1000 hours, which is equivalent to storage at room temperature for about 15 years, meeting the long-term stability requirements.
Smart Images

Figure CN119694702A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials and relates to a magnetic powder core material, in particular to a magnetic powder core material and a preparation method and application thereof. Background Art
[0002] Magnetic powder cores are widely used in telecommunications, computers, servers, control systems, photovoltaic power generation, automobiles and other fields because of their good magnetic properties in AC magnetic fields. The domestic market demand for magnetic powder cores is increasing rapidly, and the development prospects are good. In the fields where magnetic powder cores are used, the requirements for product reliability are very high. Generally defined as the product performance change rate after reliability testing cannot exceed ±10%, and the appearance cannot be rusty.
[0003] However, the magnetic powder core itself contains a large amount of Fe and a small amount of Si, Al, and Ni metal elements combined together, so the environment has a great impact on its stability. How to make the metal magnetic powder core have the function of rust prevention after coating, so that the product can have stable characteristics under high temperature and high humidity, and the prepared product can adapt to the service life of more than ten years at the client, and can meet the current use requirements in the harsh environment. This is very necessary.
[0004] CN114664509A discloses an iron-based magnetic powder with a double coating layer, a preparation method and an application thereof. The iron-based magnetic powder with a double coating layer is composed of an iron-based magnetic powder core, a phosphate coating layer and a bismaleimide resin coating layer. The magnetic powder core made of the iron-based magnetic powder with a double coating layer has the advantages of good heat resistance, low loss and low preparation cost.
[0005] CN109545537A discloses a magnetic powder and a preparation method thereof. The method comprises mixing carbonyl iron powder with a phosphating solution, and subjecting the mixture to phosphating treatment to obtain treated iron powder; drying and screening the treated iron powder, and then mixing and coating the treated iron powder with an insulating coating agent to obtain coated powder; the insulating coating agent comprises an organic resin, an inorganic coating material, a coupling agent and a curing agent; and granulating, pressing and curing the coated powder to obtain a magnetic powder core. However, the prepared magnetic powder core has poor water vapor isolation performance.
[0006] However, in the currently disclosed prior art, the ability of the magnetic powder core to isolate water vapor needs to be further improved. Therefore, how to prepare a magnetic powder core that can prevent rust is an important research direction in this field. Summary of the invention
[0007] The purpose of the present invention is to provide a magnetic powder core and a preparation method and application thereof. By optimizing the coating process formula of the material, the surface of the prepared magnetic powder core does not rust in the reliability test, and the change rate of the inductance characteristics is controlled within ±2%.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] One of the purposes of the present invention is to provide a magnetic powder core material, the surface of which is coated with a hydrophobic film. The raw materials of the magnetic powder core material include: metal magnetic powder core raw material, silica sol, phosphorus source, glue and demoulding powder.
[0010] The present invention prepares a magnetic powder core material with a hydrophobic film on the surface, which can block water vapor no matter how the magnetic powder core contacts with water vapor in the outside world, ensuring that the magnetic powder core itself does not react with water vapor in the environment, preventing the magnetic powder core from corroding and rusting, and affecting the inductance characteristics of the magnetic powder core material. The magnetic powder core prepared by the present invention can be stably stored for a long time and at a high temperature.
[0011] In the present invention, the magnetic powder core is prepared by using glue, so that the coated powder achieves an ideal granulation effect, and the ultrafine powder is easy to be molded without cracking, and a product with a complex structure can be molded.
[0012] As a preferred technical solution of the present invention, based on the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the metal magnetic powder core raw material is 96.8-98.5%, wherein the mass fraction can be 96.8%, 96.9%, 97.0%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, 98.1%, 98.2%, 98.3% or 98.4%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, based on the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the silica sol is 0.3-0.9%, wherein the mass fraction can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, based on the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the phosphorus source is 0.3-0.6%, wherein the mass fraction can be 0.3%, 0.4%, 0.5% or 0.6%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Preferably, based on the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the glue is 0.8-1.2%, wherein the mass fraction can be 0.8%, 0.9%, 1.0%, 1.1% or 1.2%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] Preferably, based on the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the demoulding powder is 0.1-0.5%, wherein the mass fraction can be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] As a preferred technical solution of the present invention, the metal magnetic powder core raw material includes any one of iron silicon, iron silicon aluminum or iron nickel, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of iron silicon and iron silicon aluminum, a combination of iron silicon aluminum and iron nickel, or a combination of iron silicon and iron nickel, etc.
[0018] Preferably, the silica sol comprises any one of kaolin, SiO2 or dicalcium phosphate or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of kaolin and SiO2, a combination of SiO2 and dicalcium phosphate, or a combination of kaolin and dicalcium phosphate, etc.
[0019] Preferably, the phosphorus source comprises phosphoric acid and / or aluminum dihydrogen phosphate.
[0020] Preferably, the glue comprises any one of silicone epoxy resin, potassium water glass, methylchlorosilane or high temperature glue, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of silicone epoxy resin and potassium water glass, a combination of potassium water glass and white powdered glue, a combination of potassium water glass and methylchlorosilane, or a combination of white powdered glue and high temperature glue, etc.
[0021] Preferably, the demoulding powder comprises any one of MgO, Al2O3 or SKZ100-B or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of MgO and Al2O3, a combination of Al2O3 and SKZ100-B, or a combination of MgO and SKZ100-B, etc.
[0022] A second object of the present invention is to provide a method for preparing the magnetic powder core material as described in the first object, the preparation method comprising:
[0023] The raw material of the metal magnetic powder core material is subjected to annealing, insulation, glue coating, demoulding and sintering in sequence to obtain the magnetic powder core material.
[0024] The present invention coats the metal magnetic powder core with glue so that a hydrophobic film is formed on the surface of the coated magnetic powder core, ensuring that after the magnetic powder core is prepared, water vapor can be blocked during the contact between the magnetic powder core and external water vapor, thereby preventing the magnetic powder core itself from reacting with water vapor in the environment, preventing the magnetic powder core from corroding and rusting, improving the inductance specificity of the magnetic powder core, and thus improving the stable storage of the magnetic powder core under long-term and high-temperature conditions.
[0025] Preferably, the annealing temperature is 900-920°C, wherein the temperature may be 900°C, 902°C, 904°C, 906°C, 908°C, 910°C, 912°C, 914°C, 916°C, 918°C or 920°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the annealed powder is subjected to a first screening.
[0027] Preferably, the D50 particle size of the first sifted powder is 5 to 35 μm, wherein the D50 particle size may be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm or 35 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] As a preferred technical solution of the present invention, the insulation method includes: first mixing the silica sol and the annealed powder.
[0029] Preferably, after the first mixing, the powder is subjected to a second screening and then phosphating.
[0030] Preferably, the mesh number of the second sieving is 70-90 mesh, wherein the mesh number can be 70 mesh, 72 mesh, 74 mesh, 76 mesh, 78 mesh, 80 mesh, 82 mesh, 84 mesh, 86 mesh, 88 mesh or 90 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the phosphating method comprises: performing a second mixing of the phosphorus source, the second sieved powder and the organic solvent.
[0032] Preferably, the organic solvent comprises any one of ethanol, acetone, NN-dimethylformamide or xylene, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of ethanol and acetone, a combination of acetone and NN-dimethylformamide, or a combination of NN-dimethylformamide and xylene, etc.
[0033] Preferably, the mass ratio of the phosphorus source to the second sifted powder is (90-99):(10-1), wherein the mass ratio can be 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2 or 99:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the temperature of the second mixing is 25-85°C, wherein the temperature can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or 85°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] The phosphating temperature in the present invention is 25-85°C.
[0036] Preferably, the solid content of the second mixture is 97-99%, wherein the solid content may be 97%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, after the second mixing, the powder is dried and sieved for the third time.
[0038] Preferably, the drying temperature is 100-140°C, wherein the temperature may be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the mesh number of the third screening is 60-100 mesh, wherein the mesh number can be 60 mesh, 65 mesh, 70 mesh, 75 mesh, 80 mesh, 85 mesh, 90 mesh, 95 mesh or 100 mesh, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] As a preferred technical solution of the present invention, the glue coating method includes: performing a third mixing of the glue, the insulated powder and the organic solvent.
[0041] Preferably, the organic solvent comprises any one of ethanol, acetone, NN-dimethylformamide or xylene, or a combination of at least two of them, wherein typical but non-limiting examples of the combination include: a combination of ethanol and acetone, a combination of acetone and NN-dimethylformamide, or a combination of NN-dimethylformamide and xylene, etc.
[0042] The invention selects a solvent with an oily group and an organic glue that can be dissolved by the oily solvent to prepare a coated magnetic powder core, and a hydrophobic film can be formed on the surface of the magnetic powder core.
[0043] Preferably, the solid content of the third mixture is 91-94%, wherein the solid content may be 91%, 91%, 93% or 94%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, after the third mixing, the powder is screened for the fourth time.
[0045] Preferably, the mesh number of the fourth screening is 60-100 mesh, wherein the mesh number can be 60 mesh, 65 mesh, 70 mesh, 75 mesh, 80 mesh, 85 mesh, 90 mesh, 95 mesh or 100 mesh, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] As a preferred technical solution of the present invention, the demoulding molding includes: adding demoulding powder to the powder after the glue coating.
[0047] Preferably, the fifth sieving is performed after adding the demoulding powder.
[0048] Preferably, the mesh number of the fifth sieve is 60-100 mesh, wherein the mesh number can be 60 mesh, 65 mesh, 70 mesh, 75 mesh, 80 mesh, 85 mesh, 90 mesh, 95 mesh or 100 mesh, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] Preferably, the molding density of the demoulding molding is greater than 5.9 g / cm 3 The molding density can be 5.9 g / cm 3 、6.0g / cm 3 、6.1g / cm 3 、6.2g / cm 3 、6.5g / cm 3 , 7.0g / cm 3 , 7.5g / cm 3 , 8.0g / cm 3 , 8.5g / cm 3 or 9g / cm 3 The above values are not limited to the above listed values, and other values not listed in the above listed values are also applicable.
[0050] Preferably, the sintering temperature is 650-750°C, wherein the temperature may be 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] As a preferred technical solution of the present invention, the preparation method comprises:
[0052] The raw material of the metal magnetic powder core material is sequentially subjected to annealing at 900-920° C., insulation, glue coating, demolding and sintering at 650-750° C. to obtain the magnetic powder core material;
[0053] The insulation method comprises: mixing silica sol and annealed powder, and then performing a second screening and phosphating in sequence; the phosphating method comprises: mixing a phosphorus source, the second screened powder and an organic solvent, and then performing drying at a temperature of 100 to 140° C. and a third screening in sequence;
[0054] The method of coating with glue comprises: sequentially mixing glue, insulated powder and organic solvent and sieving for the fourth time;
[0055] The demoulding method comprises: adding demoulding powder to the powder after the glue coating, and the molding density of the demoulding is greater than 5.9g / cm 3 .
[0056] The third object of the present invention is to provide an application of the magnetic powder core material as described in the first object, wherein the magnetic powder core is applied in the field of magnetic materials.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) The magnetic powder core prepared by the present invention can block water vapor, so that the magnetic powder core itself does not react with the water vapor in the environment, preventing the magnetic powder core from corrosion and rusting. It can be stably stored for a long time and temperature. It can be stored for 1000 hours at 85°C, which is equivalent to about 15 years at room temperature.
[0059] (2) The magnetic powder core prepared by the present invention has very fine powder, is easy to shape, does not crack, and can be molded into products with complex structures;
[0060] (3) The present invention improves the performance of the inductance characteristics, Q value, 100Oe stacking and 50K / 100mT power consumption of the magnetic powder core, wherein the magnetic permeability is 19-90, the Q can be as high as 152 or more, the 100Oe stacking ratio can be as high as 72 or more, and the power consumption can be as low as 100mw / cm 3 the following. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a cross-sectional electron microscope image of the magnetic powder core prepared in Example 1 of the present invention.
[0062] Figure 2 It is a cross-sectional electron microscope image of the magnetic powder core prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0064] Example 1
[0065] This embodiment provides a magnetic powder core, the surface of which is coated with a hydrophobic film. The raw materials of the magnetic powder core include 0.6% kaolin, 0.5% phosphoric acid, 1% silicone epoxy resin, 0.3% MgO and 97.6% iron silicon.
[0066] This embodiment provides a method for preparing the magnetic powder core, the method comprising:
[0067] The iron silicon is subjected to annealing, insulation, glue coating, demoulding and sintering in sequence to obtain the magnetic powder core material;
[0068] The annealing method includes: annealing the ferrosilicon in a nitrogen environment at 910° C. and then performing a first screening, wherein the D50 particle size of the powder after the first screening is 30 μm.
[0069] The insulation method comprises: after mixing kaolin and annealed powder, sequentially performing a second screening and phosphating, the mesh number of the second screening is 80 meshes, and the phosphating method comprises: after mixing phosphoric acid with a concentration of 50%, the powder after the second screening and acetone (solid content is 98%), sequentially performing drying at a temperature of 120° C. and a third screening, the mesh number of the third screening is 80 meshes;
[0070] The method of adding glue and coating comprises: mixing the silicone epoxy resin, the insulated powder and ethanol in sequence (solid content is 92%) and sieving for the fourth time, wherein the mesh number of the fourth sieving is 80 meshes;
[0071] The demoulding method comprises: adding MgO to the powder after the glue coating, and the molding density of the demoulding is greater than 5.9g / cm 3 ;
[0072] Sintering includes: placing the demoulding product into a sintering furnace at a sintering temperature of 700°C.
[0073] The cross-sectional electron microscope image of the magnetic powder core prepared in this embodiment is as follows: Figure 1 shown.
[0074] Example 2
[0075] This embodiment provides a magnetic powder core, the surface of the magnetic powder core material is coated with a hydrophobic film, and the raw materials of the magnetic powder core include 0.7% SiO2, 0.5% phosphoric acid, 1% potassium water glass, 0.3% Al2O3 and 97.5% magnetic powder core.
[0076] This embodiment provides a method for preparing the magnetic powder core, the method comprising:
[0077] The iron silicon is subjected to annealing, insulation, glue coating, demoulding and sintering in sequence to obtain the magnetic powder core material;
[0078] The annealing method comprises: annealing the ferrosilicon in a nitrogen environment at 900° C. and then performing a first screening, wherein the D50 particle size of the powder after the first screening is 30 μm.
[0079] The insulation method comprises: after mixing SiO2 and annealed powder, performing second screening and phosphating in sequence, wherein the mesh number of the second screening is 70 meshes; the phosphating method comprises: after mixing phosphoric acid with a concentration of 50%, the powder after the second screening and NN-dimethylformamide (solid content is 97%), performing drying at a temperature of 100° C. and third screening in sequence, wherein the mesh number of the third screening is 70 meshes;
[0080] The method of adding glue and coating comprises: mixing potassium water glass, insulated powder and NN-dimethylformamide in sequence (solid content is 94%) and sieving for the fourth time, wherein the mesh number of the fourth sieving is 70 meshes;
[0081] The demoulding method comprises: adding Al2O3 to the powder after the glue coating, and the molding density of the demoulding is greater than 5.9g / cm 3 ;
[0082] Sintering includes: placing the demoulding product into a sintering furnace at a sintering temperature of 650°C.
[0083] Example 3
[0084] This embodiment provides a magnetic powder core, the surface of the magnetic powder core material is coated with a hydrophobic film, and the raw materials of the magnetic powder core include 0.8% dicalcium phosphate, 0.5% phosphoric acid, 1% high-temperature glue, 0.3% SKZ100-B and 97.4% iron silicon.
[0085] This embodiment provides a method for preparing the magnetic powder core, the method comprising:
[0086] The iron silicon is subjected to annealing, insulation, glue coating, demoulding and sintering in sequence to obtain the magnetic powder core material;
[0087] The annealing method includes: annealing the ferrosilicon in a nitrogen environment at 920° C. and then performing a first screening, wherein the D50 particle size of the powder after the first screening is 35 μm.
[0088] The insulation method comprises: mixing dicalcium phosphate and annealed powder, and then performing a second screening and phosphating in sequence, wherein the mesh number of the second screening is 90 meshes; the phosphating method comprises: mixing phosphoric acid with a concentration of 50%, the powder after the second screening and acetone (solid content is 99%), and then performing drying at a temperature of 140° C. and a third screening in sequence, wherein the mesh number of the third screening is 100 meshes;
[0089] The method of coating with glue comprises: mixing high temperature glue, insulated powder and ethanol in sequence (solid content is 91%) and sieving for the fourth time, wherein the mesh number of the fourth sieving is 100 meshes;
[0090] The demoulding method comprises: adding SKZ100-B to the powder after the glue coating, and the molding density of the demoulding is greater than 5.9g / cm 3 ;
[0091] Sintering includes: placing the demoulding product into a sintering furnace at a sintering temperature of 700°C.
[0092] Example 4
[0093] In this embodiment, except that 0.6% of the kaolin is replaced by 0.9% and 97.6% of the iron silicon is replaced by 97.3%, other conditions are the same as those of the embodiment 1.
[0094] Example 5
[0095] In this embodiment, except that 0.5% of phosphoric acid is replaced by 0.4% and 97.6% of iron silicon is replaced by 97.7%, other conditions are the same as those in embodiment 1.
[0096] Example 6
[0097] In this embodiment, except that 0.6% of kaolin is replaced by 0.7% and 0.5% of phosphoric acid is replaced by 0.4%, other conditions are the same as those in embodiment 1.
[0098] Example 7
[0099] In this embodiment, except that 0.6% of kaolin is replaced by 0.8%, 0.5% of phosphoric acid is replaced by 0.4%, and 97.6% of iron silicon is replaced by 97.5%, other conditions are the same as those in embodiment 1.
[0100] Example 8
[0101] In this embodiment, except that 0.6% of kaolin is replaced by 0.9%, 0.5% of phosphoric acid is replaced by 0.4%, and 97.6% of iron silicon is replaced by 97.4%, other conditions are the same as those in embodiment 1.
[0102] Example 9
[0103] In this comparative example, except that 0.6% of the kaolin is replaced by 0.1% and 97.6% of the iron silicon is replaced by 98.1%, other conditions are the same as those of Example 1.
[0104] Example 10
[0105] In this comparative example, except that 0.6% of the kaolin is replaced by 1.2% and 97.6% of the iron silicon is replaced by 97%, other conditions are the same as those of Example 1.
[0106] Embodiment 11
[0107] In this comparative example, except that 0.5% of phosphoric acid is replaced by 0.1% and 97.6% of iron silicon is replaced by 98%, other conditions are the same as those of Example 1.
[0108] Example 12
[0109] In this comparative example, except that 0.5% of phosphoric acid is replaced by 1.0%, and 97.6% of iron silicon is replaced by 97.1%, other conditions are the same as those of Example 1.
[0110] Comparative Example 1
[0111] Except that the step of adding glue and coating is not performed, other conditions in this comparative example are the same as those in Example 1.
[0112] The cross-sectional electron microscope image of the magnetic powder core prepared in this comparative example is as follows Figure 2 shown.
[0113] The magnetic powder cores prepared in Examples 1-12 and Comparative Example 1 were tested for inductance characteristic change rate, Q value, 100Oe superposition, 50K / 100mT power consumption and aging degree. The test results are shown in Table 1.
[0114] The inductance and Q value are tested using the WK3260B inductor meter, and the power consumption is tested using the SY8218 power consumption tester. The specific test methods are as follows:
[0115] 1. Inductance test: L: (46.8±3.8)μH
[0116] Test conditions: CH1061A / 100KHz / 0.25V / 00.4mm / 25TS.
[0117] 2. Q value test: Q2100
[0118] Test conditions: CH1061A / 100KHz / 0.25V / p0.4mm / 25TS.
[0119] 3. Overlay test: L20A / LOA250%
[0120] Test conditions: CH1061A / 100KHz / 1V / 00.4mm / 25TS.
[0121] 4. Loss test: 50k / 100mT<100mw / cm 3
[0122] Test conditions: SY8218 N1=22Ts N2=22TS p=0.4mm 25℃.
[0123] 5. Room temperature storage test: Use the life law to design an accelerated experiment (for example, if the temperature rises according to the law of 10C, the life of the electronic product will be shortened according to the law of 2n). The present invention tests the storage time at 85°C to characterize the storage time at room temperature.
[0124] Table 1
[0125]
[0126] It can be seen from Examples 1-8 that the magnetic powder core material prepared in the present application will not react with water vapor in the environment both inside and outside due to the hydrophobic film coated on the surface, thus preventing the magnetic powder core from corroding and rusting and improving the inductance characteristics of the magnetic powder core.
[0127] By comparing Example 1 with Examples 9-10, it can be seen that when the content of silica sol is too low, the magnetic permeability of the prepared magnetic powder core material decreases, and regardless of whether the content of silica sol is too low or too high, the anti-rust performance of the prepared magnetic powder core material is slightly reduced; by comparing Example 1 with Examples 11-12, it can be seen that when the content of phosphoric acid is too high or too low, the anti-rust performance and inductance performance of the prepared magnetic powder core material are reduced.
[0128] By comparing Example 1 with Comparative Example 1, it can be seen that the magnetic powder core prepared without the glue coating step does not have the effect of preventing the magnetic powder core from reacting with water vapor in the environment.
[0129] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A magnetic powder core material, characterized in that: The surface of the magnetic powder core material is coated with a hydrophobic film, and the raw materials of the magnetic powder core material include: metal magnetic powder core raw material, silica sol, phosphorus source, glue and demoulding powder.
2. The magnetic powder core material according to claim 1, characterized in that: Taking the total mass of the raw materials of the magnetic powder core material as 100%, the mass fraction of the metal magnetic powder core raw material is 96.8-98.5%; Preferably, based on the total mass of the raw materials of the magnetic powder core material being 100%, the mass fraction of the silica sol is 0.3-0.9%; Preferably, based on the total mass of the raw materials of the magnetic powder core material being 100%, the mass fraction of the phosphorus source is 0.3-0.6%; Preferably, based on the total mass of the raw materials of the magnetic powder core material being 100%, the mass fraction of the glue is 0.8-1.2%; Preferably, based on the total mass of the raw materials of the magnetic powder core material being 100%, the mass fraction of the demoulding powder is 0.1-0.5%.
3. The magnetic powder core material according to claim 1 or 2, characterized in that: The metal magnetic powder core raw material includes any one of iron silicon, iron silicon aluminum or iron nickel, or a combination of at least two thereof; Preferably, the silica sol comprises any one or a combination of at least two of kaolin, SiO2 or dicalcium phosphate; Preferably, the phosphorus source comprises phosphoric acid and / or aluminum dihydrogen phosphate; Preferably, the glue comprises any one or a combination of at least two of silicone epoxy resin, potassium water glass, methylchlorosilane or high temperature glue; Preferably, the demoulding powder includes any one of MgO, Al2O3 or SKZ100-B or a combination of at least two of them.
4. A method for preparing a magnetic powder core material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The raw material of the metal magnetic powder core material is subjected to annealing, insulation, glue coating, demoulding and sintering in sequence to obtain the magnetic powder core material.
5. The preparation method according to claim 4, characterized in that: The annealing temperature is 900-920°C; Preferably, the annealed powder is first screened; Preferably, the D50 particle size of the first sieved powder is 5 to 35 μm.
6. The preparation method according to claim 4 or 5, characterized in that: The insulation method comprises: first mixing silica sol and annealed powder; Preferably, after the first mixing, the powder is subjected to a second sieving and then phosphating; Preferably, the mesh number of the second sieve is 70 to 90 mesh; Preferably, the phosphating method comprises: performing a second mixing of the phosphorus source, the second sieved powder and the organic solvent; Preferably, the organic solvent comprises any one of ethanol, acetone, NN-dimethylformamide or xylene, or a combination of at least two thereof; Preferably, the mass ratio of the phosphorus source to the second sieved powder is (90-99):(10-1); Preferably, the temperature of the second mixing is 25 to 85°C; Preferably, the solid content of the second mixture is 97-99%; Preferably, after the second mixing, the powder is dried and sieved for the third time; Preferably, the drying temperature is 100-140°C; Preferably, the mesh size of the third screening is 60-100 meshes.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The method of coating with glue comprises: performing a third mixing of glue, the insulated powder and an organic solvent; Preferably, the organic solvent comprises any one of ethanol, acetone, NN-dimethylformamide or xylene, or a combination of at least two thereof; Preferably, the solid content of the third mixture is 91-94%; Preferably, after the third mixing, the powder is sieved for the fourth time; Preferably, the mesh size of the fourth sieving is 60 to 100 meshes.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The demoulding molding comprises: adding demoulding powder to the powder material coated with glue; Preferably, a fifth sieving is performed after adding the release powder; Preferably, the mesh number of the fifth sieve is 60 to 100 mesh; Preferably, the molding density of the demoulding molding is greater than 5.9 g / cm 3 ; Preferably, the sintering temperature is 650-750°C.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method comprises: The raw material of the metal magnetic powder core material is sequentially subjected to annealing at 900-920° C., insulation, glue coating, demolding and sintering at 650-750° C. to obtain the magnetic powder core material; The insulation method comprises: mixing silica sol and annealed powder, and then performing a second screening and phosphating in sequence; the phosphating method comprises: mixing a phosphorus source, the second screened powder and an organic solvent, and then performing drying at a temperature of 100 to 140° C. and a third screening in sequence; The method of coating with glue comprises: sequentially mixing glue, insulated powder and organic solvent and sieving for the fourth time; The demoulding method comprises: adding demoulding powder to the powder after the glue coating, and the molding density of the demoulding is greater than 5.9g / cm 3 .
10. An application of the magnetic powder core material according to any one of claims 1 to 3, characterized in that: The magnetic powder core material is applied in the field of magnetic materials.
Citation Information
Patent Citations
Magnetic powder core and preparation method thereof
CN109545537A